Kvinnor som missgynnar andra kvinnor : En empirisk studie av 3408 ärenden om resursfördelning av bostadsanpassningsbidrag i Luleå kommun - Jonsson, Josefin; Jönsson, Isabelle (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
Equality is getting more and more attention in today’s society. Luleå kommun signed an equality declaration under the year 2013, stating that they are to work for a more equal municipality. The purpose of this study is to explain and follow up how resources are divided within a public administration as well as identify possible actions to reduce any gender differences. To answer the study’s research question and fulfil the purpose, this study has investigated how grant for housing adaptation is divided between men and women in Luleå kommun. An abductive method has been used where previous theories have been used to support and explain the result. The study consists of two substudies. The first substudy consisted of 3408 cases regarding grant for housing adaptation in Luleå kommun from the year 2012 to 2017. The result shows that when the certifier of the adaption were a woman, the men that applied for the grant got a bigger sum of money than the women. A significant difference could also be seen when the certifier had the profession of an occupational therapist. To find explanations and comprehension for the result of the first substudy, the second substudy were a post-hoc analysis that consisted of semi structured interviews. Three female occupational therapists, two office workers, the chief off the section were the grant are granted and one gender researcher, all in Luleå kommun, were interviewed. The conclusion of the study is that the historic power relationship between men and women are the underlying cause for the imbalanced resource allocation. The study contributes with a concrete control method. We suggest changed working manners with adoption of checklists and new routines are required. It’s important that the result from this study are brought to the surface in order for change to happen. Lastly follow-ups are required for the gender equality work to move forward.